Dramatic toughness improvement of poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) by supercritical carbon dioxide–assisted annealing. (15th May 2021) - Chen, Lina; Mao, Rongshui; Zhang, Li; Xu, Jinke; Li, Delong; Bao, Jinbiao; Wang, Zongbao
Abstract: Supercritical carbon dioxide (scCO2 )–assisted annealing process has demonstrated promising prospects in the toughness enhancement of polymers. Herein, this effective method was adopted to toughen a biodegradable polymer, poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) (PHBV). Significantly, the greatly improved tensile toughness and impact toughness of PHBV were achieved. It is noted that the 26 times enhancement in tensile toughness and 2.4 times improvement in impact toughness were obtained for the sample treated at annealing temperature of 90°C and saturation pressure of 10 MPa. More importantly, the toughness mechanism was further explored via various characterizations. It is indicated that the increment in the toughness of PHBV after scCO2 ‐assisted annealing was closely related to the perfection of microstructure sample and the appearance of micro‐voids.